(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The purpose of this paper is to explore the factors of online learning basically those arenecessity in lockdown periodfor the student’s satisfaction during lockdown due to COVID19 and theirimpact on student’s satisfaction. Classroom study has entirely been closed and students are studyingfrom their home through the online methods. By the existing literature review five factors were identified(i) availability of study material(ii) User friendly Resources (iii)Covering Syllabus (iv) Extra Time(v) EasyAccessibility. 527 respondents were taken from across the country (India) to conduct the study. Therandom sampling method has been used for collecting the samples. The analyzed data indicates that theoverall satisfaction of students by online learning mainly depends on five factors. To meet objective datawere collected through questionnaire and to make data more meaningful and understandable analyzedthrough suitable statistical tools viz. regression, mean, standard deviation, and counts with thestatistical software SPSS 22.0. R- Squared value is .571, this indicates that the explained variance ofoverall satisfaction is 57.1 percent and the rest of the variance of overall satisfaction is unexplained. Thestudy found that the overall satisfaction of the students r2=.57 and model is statistically fit means onlinelearning moderately satisfied with the students.